Organic Agriculture in Michoacan, Mexico: Sustainability Evidence (2022)
Organic agriculture is considered an activity that favors the environment and the well-being of ecosystems and society, as well as the economy. The aim of this research is to identify and analyze some contributions that organic agriculture has generated on sustainability. To do this, the fruit sector in Michoacán was considered a case study, which is the largest contribution to organic agriculture at the national level. The method used was the revision, description, and analysis of statistical data in national databases specializing in organic agriculture, as well as the application of semi-structured interviews to organic producers in the state. According to the results obtained, it can be noted that even though organic agriculture represents a small percentage of conventional agriculture, it is an activity that is experiencing a growing trend and potential demand. Evidence shows that such activities benefit the three dimensions of sustainability, in economic, environmental and social terms, and it can be concluded that such activities contribute favorably to sustainability.